MICROBIAL EVALUATION OF NORMAL SALINE USED BY CONTACT LENS WEARERS - CHUA SIEW SIANG; SYIREEN ALWI; NGEOW YUN FONG; PIREHMA A/P MARIMUTHU (Universiti Sains Malaysia, 2006)
Contact lens solutions should only be used for four weeks after first opening but this practice is not always followed. Therefore, the present study was conducted to determine the duration that contact lens wearers could use their normal saline without microbial contamination. Two brands of normal saline, OpticareTM and Klean & KareTM, were used by 30 contact lens wearers on alternate days. Samples were collected weekly for microbial evaluation. On an average, the duration of use without microbial contamination was four weeks. Half of the participants were able to use both bottles of their normal saline without microbial contamination for at least four weeks after first opening and this included nine participants who were able to use for at least eight weeks. The brands of normal saline, the frequency of use, the place where the normal saline was stored or used were not significantly related to the duration of contamination-free period. Of the 27 samples tested, 11 grew gram-positive bacteria and 16, gram-negative bacteria. The most common bacteria found were Staphylococcus aureus and Pseudomonas species. None of the samples had Acanthamoeba spp. and no eye infection or irritation was reported. It was concluded that on an average, a bottle of sterile normal saline can be used for at least four weeks after first opening. Some users may be able to extend this expiry date to eight weeks, depending on the way the solution was used.